FRACTIONATION OF SELENIUM ISOTOPES DURING BACTERIAL RESPIRATORY REDUCTION OF SELENIUM OXYANIONS - Herbel M.J.; Johnson T.M.; Oremland R.S.; Bullen T.D. (My University, 2000)
Reduction of selenium oxyanions by microorganisms is an important process in the biogeochemical cycling of selenium. Numerous bacteria can reduce Se oxyanions, which are used as electron acceptors during the oxidation of organic matter in anoxic environments. In this study, we used a double spike (82Se and 74Se) thermal ionization mass spectrometry technique to quantify the isotopic fractionation achieved by three different species of anaerobic bacteria capable of accomplishing growth by respiratory reduction of selenate [SeO42- or Se(VI)] or selenite [SeO32- or Se(IV)] to Se(IV) or elemental selenium [Se(0)] coupled with the oxidation of lactate. Isotopic discrimination in these closed system experiments was evaluated by Rayleigh fractionation equations and numerical models. Growing cultures of Bacillus selenitireducens, a haloalkaliphile capable of growth using Se(IV) as an electron acceptor, induced a 80Se/76Se fractionation of -8.0 +/- 0.4%% (instantaneous ε value) during reduction of Se(IV) to Se(0). With Bacillus arsenicoselenatis, a haloalkaliphile capable of growth using Se(VI) as an electron acceptor, fractionations of -5.0 +/- 0.5%% and -6.0 +/- 1.0%% were observed for reduction of Se(VI) to Se(IV) and reduction of Se(IV) to Se(0), respectively. In growing cultures of Sulfurospirillum barnesii, a freshwater species capable of growth using Se(VI), fractionation was small initially, but near the end of the log growth phase, it increased to -4.0 +/- 1.0%% and -8.4 +/- 0.4%% for reduction of Se(VI) to Se(IV) and reduction of Se(IV) to Se(0), respectively. Washed cell suspensions of S. barnesii induced fractionations of -1.1 +/- 0.4%% during Se(VI) reduction, and -9.1 +/- 0.5% for Se(IV) reduction, with some evidence for smaller values (e.g., -1.7%%) in the earliest-formed Se(0) results. These results demonstrate that dissimilatory reduction of selenate or selenite induces significant isotopic fractionation, and suggest that significant Se isotope ratio variation will be found in nature.